Mathematics teachers' attitude toward mathematics teaching in secondary schools in Thailand - Aujit, Pattanajak (1978)
This study was undertaken to gather data on the attitudes of Thai Mathematics teachers regarding the subject. It aimed to find out the relation of age, sex, and education to attitudes towards mathematics. The subjects were 276 Thai Mathematics teachers from 100 public secondary schools in Thailand. The questionnaire used to gather data was composed of 18 items and divided into two parts, the first concerned with personal data and the second part with attitudes and perceptions. Findings revealed that attitude towards mathematics and mathematics teaching is not related to sex, age, and educational background.